2004
DOI: 10.1007/s10709-004-1442-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis of the mouse genome: an overview

Abstract: The careful comparison of the phenotypic variations generated by different alleles at a given locus, including of course, those alleles with a deleterious effect, is often an important source of information for the understanding of gene functions. In fact, every time it is possible to match a specific alteration observed at the genomic level with a particular pathology, it is possible to establish a relationship between a gene and its function. When considered from this point of view, the production of new mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 71 publications
(47 reference statements)
2
11
0
3
Order By: Relevance
“…Several previous studies have shown an abundance of TA–CG transitions and TA–AT transversions (ranging between 36–43% and 22–44% of changes, respectively [2,12,14,19]) and GC–CG transversions very rarely or never occur [14]. Of the validated 31 true-positive SNVs shown in table 1, 35.5, 38.7 and 0 per cent were TA–CG, TA–AT and GC–CG changes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have shown an abundance of TA–CG transitions and TA–AT transversions (ranging between 36–43% and 22–44% of changes, respectively [2,12,14,19]) and GC–CG transversions very rarely or never occur [14]. Of the validated 31 true-positive SNVs shown in table 1, 35.5, 38.7 and 0 per cent were TA–CG, TA–AT and GC–CG changes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…ENU induces high frequencies of point mutations and is a more potent mutagen than EMS. ENU, which is an alkylating agent, leads to mispairing and, ultimately, results in base pair substitutions and, sometimes, base pair losses (Guénet 2004). In the cases of rats ( R. norvegicus ) and mice ( Mus musculus ), ENU is supplied at the dose of 50–100 mg/kg (Smits et al 2004 and Nolan et al 2000, respectively), whereas in a zebrafish ( D. rerio ) TILLING experiment, the mutagen was applied at a concentration of 3 mM (Wienholds et al 2003).…”
Section: Mutagensmentioning
confidence: 99%
“…The availability of high throughput sequencing data now makes “systems genetics” a possibility with the use of large-scale forward genetic screens for novel gene discovery (Caruana et al 2013; Hill et al 2013). Forward genetic screens in mice and other model organisms with chemical mutagenesis using ethylnitrosourea (ENU) has yielded new insights into the genetic basis for a wide spectrum of biological and disease processes (Arnold et al 2011; Guenet 2004), including genes that can cause congenital heart disease (CHD) (Shen et al 2005; Yu et al 2004; Zhang et al 2009). …”
Section: Introductionmentioning
confidence: 99%